2019
DOI: 10.1590/s1517-707620190003.0718
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization effect of kraft lignin into PBAT:Thermal analyses approach

Abstract: Sterically hindered phenols are an important class of synthetic antioxidants for polymers, commonly incorporated to inhibit polyolefins or polyesters oxidation. However, synthetic antioxidants use is under restricted regulation due to their potential health risk and environmental impacts. Thus, great interest has been attracted to the phenol-based natural antioxidant such as lignin. This work aimed to evaluate the thermostability of kraft lignin (KL) as a natural antioxidant when incorporated into poly(butylen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
(22 reference statements)
0
4
0
1
Order By: Relevance
“…Working on natural rubber modification, Gregorová et al [ 166 ] showed that the lignin addition also increased the thermo-oxidative long-term resistance. On the contrary, Tavares et al [ 167 ] reported that a simple 1% lignin addition reinforces the poly(butylene adipate-co-terephthalate) matrix. On the other hand, Lisperguer et al [ 168 ] demonstrated that lignin addition to recycled polystyrene could provide similar characteristics to the native polymer.…”
Section: Lignocellulosic Materials For the Production Of Biofuels Bio...mentioning
confidence: 99%
“…Working on natural rubber modification, Gregorová et al [ 166 ] showed that the lignin addition also increased the thermo-oxidative long-term resistance. On the contrary, Tavares et al [ 167 ] reported that a simple 1% lignin addition reinforces the poly(butylene adipate-co-terephthalate) matrix. On the other hand, Lisperguer et al [ 168 ] demonstrated that lignin addition to recycled polystyrene could provide similar characteristics to the native polymer.…”
Section: Lignocellulosic Materials For the Production Of Biofuels Bio...mentioning
confidence: 99%
“…27 Several researchers used lignin, a phenolic polymer, as a suitable and cheap natural antioxidant for polyesters with regard to the weathering of PLA 28 and the thermo-oxidation of polybutylene adipate terephthalate. 29 An environment-friendly and cost-effective strategy for polymer stabilization is the use of vegetal extracts containing molecules of interest, such as polyphenol natural antioxidants. Investigations are conducted on the valorization and exploitation of biowaste and agri-food byproducts as a resource of high-value additives.…”
Section: Introductionmentioning
confidence: 99%
“…Within the tannins class, tannic acid procured an effective thermal stabilization of PHB, constituting a promising thermal and processing stabilizer . Several researchers used lignin, a phenolic polymer, as a suitable and cheap natural antioxidant for polyesters with regard to the weathering of PLA and the thermo-oxidation of polybutylene adipate terephthalate …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Outra característica das embalagens ativas é o tipo de polímero utilizado, logo, aliando as questões ambientais e econômicas [8], o poli (butileno adipato co-tereftalato) (PBAT), vem sendo estudado como uma alternativa para substituição dos polímeros convencionais. O PBAT é um copoliéster alifático-aromático produzido por reação de condensação a partir do 1,4 butanodiol, ácido adípico e ácido tereftálico, apresenta boas propriedades térmicas e mecânicas, sendo similar as características encontradas no polietileno de baixa densidade [9]. O PBAT tem como nome comercial ECOFLEX, sendo produzido pela BASF (Alemanha).…”
Section: Introductionunclassified